Custom-made health-care: An experimental investigation - Claudia Keser; Claude Montmarquette; Martin Schmidt; Cornelius Schnitzler (Health Economics Review, 2020)
Background: Physicians' financial interests might conflict with the best service to patients. It is essential to gain a thorough understanding of the effect of remuneration systems on physician behaviour. Methods: We conducted a controlled laboratory experiment using a within-subject design to investigate physician behaviour underpayment heterogeneity. Each physician provided medical care to patients whose treatments were paid for under fee-for-service (FFS) or capitation (CAP). Results: We observed that physicians customized their care in response to the payment system. FFS patients received considerably more medical care than did CAP patients with the same illness and treatment preference. Physicians over-served FFS patients and under-served CAP patients. After a CAP payment reduction, we observed neither a quantity reduction under CAP nor a spillover in FFS patients' treatment. Conclusions: The results suggest that, in our experimental model, fee regulation can be used to some extent to control physician spending since we did not identify a behavioural response to the CAP payment cut. Physicians did not recoup lost income by altering treatment behaviour toward CAP and/or FFS patients. Experimental economics is an excellent tool for ensuring the welfare of all those involved in the health system. Further research should investigate payment incentives as a means of developing health care teams that are more efficient.
Keywords: 330; Experimental economics; Physician reimbursement; Capitation; Fee-for-service; Fee regulation